2007
DOI: 10.1074/jbc.m608874200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Regulates Internal Initiation of Translation of the GATA-4 mRNA following Vasopressin-induced Hypertrophy of Cardiac Myocytes

Abstract: GATA-4 is a key member of the GATA family of transcription factors involved in cardiac development and growth as well as in cardiac hypertrophy and heart failure. Our previous studies suggest that GATA-4 protein synthesis may be translationally regulated. We report here that the 518-nt long 5-untranslated region (5-UTR) of the GATA-4 mRNA, which is predicted to form stable secondary structures (؊65 kcal/mol) such as to be inhibitory to cap-dependent initiation, confers efficient translation to monocistronic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
(82 reference statements)
1
16
1
Order By: Relevance
“…Our study showed that AVP-induced cardiomyocyte hypertrophy was suppressed in primary culture from V1aR-KO mice, confirming the involvement of the V1a receptor in cell proliferation (221). In the cellular model of cardiomyocyte hypertrophy, AVP promotes translation of the transcription factor GATA-4 through PKC in H9c2 ventricular myocytes (455). Since the V1a receptor is widely expressed in various malignant cells, including neuroendocrine tumors (377) and small cell lung cancer (SCLC) (319), the AVP/V1a receptor axis may represent a novel target for new tumor therapies.…”
Section: Protein Synthesis and Turnoversupporting
confidence: 74%
“…Our study showed that AVP-induced cardiomyocyte hypertrophy was suppressed in primary culture from V1aR-KO mice, confirming the involvement of the V1a receptor in cell proliferation (221). In the cellular model of cardiomyocyte hypertrophy, AVP promotes translation of the transcription factor GATA-4 through PKC in H9c2 ventricular myocytes (455). Since the V1a receptor is widely expressed in various malignant cells, including neuroendocrine tumors (377) and small cell lung cancer (SCLC) (319), the AVP/V1a receptor axis may represent a novel target for new tumor therapies.…”
Section: Protein Synthesis and Turnoversupporting
confidence: 74%
“…The primer sequences are as follows: forward primer, 5 ¶-GAGAAGTATCCTCAAACATTTG-3 ¶; reverse primer, 5 ¶-GCATTATGCTGAGTGATATCCCGCTCAGGATTCAGCAGATG-TATC-3 ¶. An antisense riboprobe was used to visualize 18S rRNA levels (27). For quantitative reverse transcription PCR, total RNA was reverse transcribed with random primers using the RETROscript Kit from Ambion.…”
Section: Methodsmentioning
confidence: 99%
“…Arginine vasopressin is an endogenous peptidic hormone and a stimulator of hypertrophy in cardiomyocytes 19,20 as well as in H9c2 cells. 21,22 Hypertrophy was induced by treatment of confluent H9c2 cells in 24 wells (2ϫ10 4 cells) with arginine vasopressin in Dulbecco's modified Eagle's medium with 0.25% fetal calf serum. Medium was replaced daily.…”
Section: Cell Culturementioning
confidence: 99%
“…For the subsequent kinase inhibition experiments, the concentration of arginine vasopressin was set to an excess of 1 mol/L as described previously. 21, 22 An ATPGlow cell viability assay (Promega) demonstrated cell viability rates of Ͼ85% at sorafenib or imatinib concentrations Ͻ1 mol/L. At concentrations Ͼ1 mol/L, however, viability rates decreased to 4% and 0% (sorafenib) and were 114% and 56% (imatinib) at 3 and 10 mol/L, respectively.…”
Section: Cell Culturementioning
confidence: 99%